(untitled) (Revista Archai, 2026)
he article shows that several studies on the meaning of νοῦς, νόησις, νοεῖν, and derivatives in pre-Platonic literature, especially in Homer, but also in some pre-Socratic thinkers, have concluded that these terms are never used in strictly abstract situations, but, on the contrary, always appear linked to emotions connected to concrete events. Plato is certainly the main “author” to be studied when it comes to the use of this terminology in cognitive functions. Indeed, he was the first to systematize a specialized vocabulary for these functions, and emphatically use these terms in passages of the Middle dialogues, when, according to Aristotle’s account of his Philosophy, in Metaphysics A 6, unlike Socrates, he began to suppose that the essence (οὐσία) of things is not in the things themselves, but lies beyond them, thus creating a separation (χωρισμός) which will be the fundamental source of all the difficulties concerning the “Theory of Ideas”. After hypothesizing the existence of the Ideas, abstract entities he considered more real than material ones, he created a special type of apprehension capable of capturing invisible, intelligible entities, νόησις, thus introducing a new dimension of reality: a previously non-existent, invisible, and radically abstract one. Based on these assumptions, the article ends by raising a series of questions to be addressed in a future approach to the same subject.